Imuno-histoquímica para o diagnóstico precoce de vitiligo - Nai, Gisele Alborghetti [UNESP]; Miot, Luciane Bartoli Donida [UNESP]; Miot, Hélio Amante [UNESP]; Marques, Mariângela Esther Alencar [UNESP] (My University, 2008)
Vitiligo is a frequent skin disease that affects 7 % of the population. It presents depigmented macules resulting from a gradual loss of melanocytes in the epidermis. In most cases, the diagnosis is made by clinical examination. Skin biopsies are performed when it is necessary to compare it with other hypomelanosis. Histopathological diagnosis of vitiligo is often difficult in hematoxylin-eosin (HUE) stained sections. There are a few studies on the improvement of diagnostic quality in vitiligo. Objective: To evaluate the use of immunohistochemical markers, such as S-100 protein, human melanoma black-45 (HMB-45) and Melan-A, in the early diagnosis of clinically suspected or doubtful cases of vitiligo. Materials and methods: Histological sections of biopsies from healthy and affected skin areas from 10 patients clinically suspected of vitiligo. The samples were stained with H&E, S-100 protein, HMB-45 and Melan-A methods. Counterstaining with Ciemsa was applied as a technical modification to differentiate melanin from immunolabelling. Results: Six cases with recent clinical manifestation showed lymphocyte infiltrates, such as interface dermatitis, in the affected skin in the HUE staining technique. S-100 protein, HMB-45 and Melan-A staining marked the basal layer melanocytes of the healthy skin and S-100 protein antigen evidenced Langerhans cells. Melanocytes were absent or less frequent in affected skin areas in comparison with normal skin. S-100 protein showed a larger number of Langerhans cells, what is a common feature of vitiligo lesions. Conclusion: Immunohistochemistry may be used as an auxiliary technique for the diagnosis of suspected vitiligo cases.
Immunohistochemistry for early diagnosis of vitiligo
Keywords: Cutaneous hypomelanosis; Diagnosis; Immunohistochemistry; Melan-A; Vitiligo